If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -3) = 4 Reorder the terms: (-3 + 4x) = 4 Remove parenthesis around (-3 + 4x) -3 + 4x = 4 Solving -3 + 4x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 4x = 4 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = 4 + 3 4x = 4 + 3 Combine like terms: 4 + 3 = 7 4x = 7 Divide each side by '4'. x = 1.75 Simplifying x = 1.75
| 4senx-cosx=2 | | 3x+20=74 | | 2sen(5x)=2 | | 2x^2+x-2730*2=0 | | x^4-72x^2-x-1280=0 | | 3sinhx+4coshx=4 | | 4/3=6x | | x-0.15x=35000 | | x-0.35x=35000 | | 0.4(2-9)=0.2(4+7) | | x=2x+3x+5x | | 2x^2+21x+27=500 | | 36-96x+64x^2=0 | | 2(x-3)+3(x-4)=2-5(x-2)+10 | | -35=5-19 | | x(x+4)=68 | | -2z+3z=7z-7-3z | | 68+45+79+75+x=180 | | -25=225 | | 27a^2+18a+3=0 | | -8v=160 | | 100+68+60+45+x=180 | | 7x^2-31x-272=0 | | 20+35+156+x=180 | | -7=1+b | | 115+115+85+x=180 | | 3x-3=-4x-6 | | -20m=-80 | | 27+x+35+23=180 | | X^2+6x+10=-2x-6 | | C^3-10=17 | | 60+65+50+35+x=180 |